Daring to process the trauma: using a web-based training to reduce psychotherapists' fears and reservations around implementing trauma-focused therapy. Issue 1 (31st December 2019) - Sansen, Lisa M.; Saupe, Laura B.; Steidl, Annika; Fegert, Jörg M.; Hoffmann, Ulrike; Neuner, Frank
ABSTRACT: Although trauma-focused interventions are the first-line therapies for patients with posttraumatic stress disorder (PTSD), they are not frequently used in clinical practice. Factors preventing therapists from applying trauma-focused methods include a lack of training and negative attitudes towards trauma-focused therapy. The aim of the present study was to investigate which factors predict willingness to carry out trauma-focused therapy and to examine whether a web-based training is able to reduce negative attitudes and reservations about these interventions. In a wait-list controlled evaluation study, therapists ( N = 499) were randomized into an intervention or a wait-list control group. Results show that trauma-treatment specific competencies and overcoming pre-existing concerns towards trauma-focused therapy significantly predict therapists' willingness to utilize trauma-focused interventions. Thus, the content alignment of the web-based course is appropriate for improving therapists' willingness to conduct trauma-focused therapy. A retrospective examination of therapists after the training and a comparison of fears and reservations before and after the training demonstrate a significant reduction of fears and reservations. In terms of perceived contraindications, no effects of the web-based training were found. The present study provides compelling evidence that web-based training in evidence-based PTSD therapy is able to reduce reservations that may prevent therapists from applying evidence-based trauma-focused interventions. HIGHLIGHTS: Web-based training in trauma therapy increases therapists' knowledge and skills. leads to a modification of negative attitudes preventing therapists from applying trauma-focused interventions. improves the willingness to conduct trauma-focused therapy.